Paying attention to climate design and creating conditions for using new energies in the building, a step towards green architecture - Mahdi Beyragh Shamshir; Elham Sarkardehi (مهندسی و مدیریت ساخت)
The need for energy has been one of the most important concerns of human life, and today, with the industrialization of cities and the increase in population, followed by the increase in demand for the use of energy, its importance in life has increased more than before. Also, due to the problems that exist in the use of non-renewable energies, such as the limited nature of these resources and environmental pollution, the countries that are facing environmental crises and droughts, the use of alternative energies and their utilization is a necessity. count Renewable energies, which include diverse, free, available and non-polluting resources, are the best solution to replace fossil fuels. Green architecture proposes a plan for the future that aims to build green buildings with emphasis on the optimal use of energy and preventing its waste in order to provide cooling and heating and preserve it for future generations as well as prevent the negative effects of construction and It is an instrument on the environment. The requirement for the realization of this is the use of native architecture, which the architects of the past, by adapting to the climatic conditions and their designs, provided the best conditions for human comfort and peace. Buildings are one of the things that have the most energy loss and have a significant impact on environmental pollution and human health. In the upcoming research, using library resources, the application of renewable energy in the design of buildings will be investigated considering climate issues.